RESONATOR-BASED METERING OF POWER COMPONENTS ACCORDING TO IEEE STANDARD 1459-2010 - Kušljević , Miodrag; Tomić, Josif; Poljak, Predrag (Journal on Processing and Energy in Agriculture, 2021)
This paper proposes an accurate and computationally efficient implementation of the IEEE Std. 1459-2010 for power measurements. An implementation is based on digital resonators embedded in a feedback loop. In the first algorithm stage, the unknown signal harmonic parameters are estimated. By this, the voltage and current signals are processed independently on each other. In the second algorithm stage, the unknown power components are estimated (calculated) from based on estimated spectra. To demonstrate the performance of the developed algorithm, computer simulated data and laboratory testing records are processed. Simple LabView implementation, based on point-by-point processing feature, demonstrates techniques modest computation requirements and confirms that the proposed algorithm is suitable for real–time applications.
Keywords: IEEE Standard 1459–2010, power quality (PQ), power measurement, harmonic analysis, recursive algorithm, adaptive filtering, resonator filters, decimation filters, finite-impulse-response (FIR) filter, virtual instrument (VI), real-time system, point-by-point analysis.